(untitled) - Elizabeth Laird (Essex, UK, 1994)
This book is an introduction to some of places you might want to visit, and some of the things you might want to know. It gives a new look at national life: work and leisure, government, sport, music and family life as well as places of interest; practical information to both countries; a helpful guide to social occasions and meeting people
Keywords: gt.britain - description and travel,gt.britain - history